Um osso para rex: as relações entre consumidor e animais de estimação e as suas influências no ato de presentear - Mitidieri, Luciana Uchôa (2006)
The objective of the present work is to investigate gift-giving behavior between humans and their pets, and whether the relationship between human and pet affects the choice and purchase of these gifts. Theoretical support comes from works by Wolfinbarger (1990) who categorized the motivations underlying gift-giving, Belk & Coon (1993) who observed gift-giving as an economic exchange, Belk (1993) who approached gift-giving as an act of agapic love, and finally Hirschman (1994) who described many forms of relationship between consumers and their pets. The present study is of exploratory character. In-depth interviews were conducted so then the feelings and emotions of the informants, necessary to the analysis, could emerge. It was assumed that agapic, unconditional love, guided the gifts choice and purchase. Nevertheless, interpretation of the records shows that motivations which led the humans to give gifts to their pets were many. The work shows these motivations in a matrix. Records also indicate that it is difficult to establish the threshold between on motivation and the other.